Studies on cryopreservation of cauda epididymal spermatozoa buffaloes - HARSHAN, HIRON M; SINGH, L P (The Indian Journal of Animal Reproduction, 2023)
The effect of cryopreservation on the viability, motility, acrosomal integrity, cervical mucus penetration ability and response to hypo-osmotic solution was studied on samples of cauda epididymal semen collected from 12 mature buffalo bulls slaughtered at the local slaughter house. Though a significant reduction (P<0.05) in all the parameters was observed after cryopreservation it was concluded that successful cryopreservation of the cauda epididymal semen can be done. The viability, motility, acrosomal integrity, cervical mucus penetration ability and response to hypo-osmotic solution were reduced from 83.92±0.80%, 72.75±0.91%, 80.42±0.82%, 21.17±0.75 mm and 72.00±0.93%to 68.67±0.94%,51.58±1.18%, 66.83±1.05%, 17.67±0.84 mm and 59.67±0.85%, respectively .